2001
DOI: 10.2355/isijinternational.41.1494
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemical Composition and Oxidation Temperature on the Adhesion of Scale in Plain Carbon Steels.

Abstract: Effects of chemical composition and oxidation temperature on blistering and delaminating of scales formed on steels were investigated. The scale blistering occurred for steels with P content above 0.005 mass%. Low carbon steels with 0.01mass%Si-0.2mass%Mn-0.01mass%P showed pronounced blistering at 1 223 K. The temperature at which the time to blistering is the shortest, the prominent temperature, decreased with increasing Mn and P contents and deceasing Si content in steels. There was no effect of C, S and sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…In one case, blistering is believed to be caused by stress generated during scale formation. [1][2][3][4] In the other case, gas generation at the scale/steel interface is thought to lead to the formation of blisters. 1,2,5) It was suggested that not only CO and CO2, but also N2, play a role in the blistering phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…In one case, blistering is believed to be caused by stress generated during scale formation. [1][2][3][4] In the other case, gas generation at the scale/steel interface is thought to lead to the formation of blisters. 1,2,5) It was suggested that not only CO and CO2, but also N2, play a role in the blistering phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…12). It is reported that blistering is caused by the stress generated during scale formation [1][2][3][4] and also gas release at the scale/ steel interface. 1,2,5,6) The experimental result of blister internal gas measurement supports the latter idea.…”
Section: Nucleationmentioning
confidence: 99%
“…The separated steel surface does not oxidize at this stage, which explains why N 2 gas remains inside the blisters as described above. In this growth process the main driving force of blistering may be scale growth stress [1][2][3][4] or N 2 gas release.…”
Section: Growthmentioning
confidence: 99%
See 2 more Smart Citations